Les Annales du théâtre et de la musique vols. 1-28, 30, 32, 33, 36-38 - Noël, Edouard; Stoullig, Edmond (Paris Charpentier Ollendorf, 1876)
Les Annales du théâtre et de la musique was an annual French periodical that covered French theatre and opera from 1875 to 1916. Edited by Édouard Noël (1848-1926) and Edmond Stoullig (1845-1918), it was published by Charpentier from 1876 to 1895, by Berger-Levrault in 1896 and by Paul Ollendorff from 1897 (with Stoullig as sole editor). The penultimate volume was published in 1916 (covering the years 19141915) and the last in 1918 (covering the year 1916), making a total of 41 volumes.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Periodical; Theater criticism; Music criticism; Paris (France)